2020
DOI: 10.3989/gya.0463191
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, oxidative stability, and sensory properties of <em>Boerhavia elegana Choisy</em> (alhydwan) seed oil/peanut oil blends

Abstract: This study investigated the effects of blending alhydwan seed oil and peanut oil as a way of enhancing the stability and chemical characteristics of plant seed oils and to discover more innovative foods of high nutraceutical value which can be used in other food production systems. Alhydwan seed oil and peanut oil blended at proportions of 10:90, 20:80, 30:70, 40:60 and 50:50 (v/v) were evaluated according to their physi­cochemical properties, including refractive index, relative density, saponification value,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These observations agree with the statement of [ 24 ] who suggested that an increase in the peroxide value of oils would be due to the formation of hydroperoxides by degradation of the double bonds of fatty acids, while a drop would be attributed to low production or the volatilization of compounds resulting from the decomposition of hydroperoxides formed during the primary oxidation phase. In addition [ 25 ], demonstrated that mixtures of Boerhavia and groundnut seed oils as well as mixtures of moringa, sunflower and soybean oils, treated at a high temperature (180 °C/2 h) gave low peroxide values (6.97–6.02 meq O 2 /kg of oil). Also, it has been observed a decrease of peroxide value in a mixture made up of sesame and corn oils during frying, compared to that of sesame oil alone, and this was associated to the proportion of saturated fatty acid present in corn oil [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…These observations agree with the statement of [ 24 ] who suggested that an increase in the peroxide value of oils would be due to the formation of hydroperoxides by degradation of the double bonds of fatty acids, while a drop would be attributed to low production or the volatilization of compounds resulting from the decomposition of hydroperoxides formed during the primary oxidation phase. In addition [ 25 ], demonstrated that mixtures of Boerhavia and groundnut seed oils as well as mixtures of moringa, sunflower and soybean oils, treated at a high temperature (180 °C/2 h) gave low peroxide values (6.97–6.02 meq O 2 /kg of oil). Also, it has been observed a decrease of peroxide value in a mixture made up of sesame and corn oils during frying, compared to that of sesame oil alone, and this was associated to the proportion of saturated fatty acid present in corn oil [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the tocopherol level in all blends was found to be greater compared to the findings of Siddeeg and Xia (2015) , who reported a range of 580–693 mg/kg for the total tocopherol content in Seinat seed oil and peanut oil blends. Likewise, Al-Farga et al (2020) claimed a range of total tocopherol levels from 580 to 719 mg/kg in the blends of alhydwan seed oil and peanut oil.…”
Section: Resultsmentioning
confidence: 99%
“…Results also showed a typical decrease in flavor score values during storage at 60 °C, indicating that the examined oils would receive relatively low acceptance as edible oil without further refinement ( Table 4S , S1). This could be due to the fact that storage at elevated temperatures negatively affects flavor stability, and results in poor oxidation properties ( Al-Farga et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vegetarian source of essential fatty acid (omega-3) is very limited. In recent years, the need for unconventional oils has increased due to their bioactive components and essential fatty acid composition (Al-Farga et al, 2020). Perilla frutescens is an underutilized herb of the mint family (Lamiaceae), mainly found in Asian countries like China, Japan, Thailand, and India.…”
Section: Introductionmentioning
confidence: 99%